ECONOMIC EMPOWERMENT OF THE COMMUNITY OF BATU LAYANG CISSARUA VILLAGE, BOGOR - Achmad Jaelani; Winaya Purwanti; Hastuti Indra Sari; Safrudin; Bambang Santosa; Arsid; Harnovinsah (RADJA PUBLIKA, 2024)
Micro, Small, and Medium Enterprises (MSME) Skills Training has been implemented in Batu Layang Village, Cisarua Subdistrict, Bogor, to increase local communities' economic empowerment. This program aims to provide knowledge and skills to Batu Layang Village residents so they can manage small and medium businesses more effectively. The training method involves workshops, practical training, group discussions, and direct mentoring by experts in the MSME field. The training results showed a significant increase in participants' knowledge and skills, increased income, and the opening of new jobs at the local level. An evaluative discussion regarding the program's success was carried out, including identifying challenges faced and recommendations for strengthening the program's sustainability in the future. This program has had a significant positive impact on the economic empowerment of the Batu Layang Village community and can be an example of similar efforts in other areas.